Dialog Hukum Adat dan Islam: Kritik Syeikh Ahmad Khatib Al-Minangkabawi Terhadap Sistem Waris di Minangkabau - Arif, Muhammad Fahmil; Rahmi, Melvi; Endriyenti, Endriyenti (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research discusses the two main forces influencing Minangkabau society, namely custom and religion. The matrilineal system practiced in Minangkabau has significant differences compared to the Islamic kinship system, particularly in terms of inheritance distribution. These differences often become a source of conflict and academic interest, especially among scholars of Islamic law. One figure who firmly opposes the customary inheritance system in Minangkabau is Sheikh Ahmad Khatib al-Minangkabawi, a prominent scholar who served as Imam, Khatib, and teacher in Mecca. This study employs a library research approach with a descriptive analytical method to explore Sheikh Ahmad Khatib's critiques of the prevailing inheritance system. Sheikh Ahmad Khatib argues that customary practices that divert inheritance to nephews rather than biological children contradict Islamic principles. He even equates this action with consuming the wealth of orphans, a deed prohibited in Islam. During his time, there was ambiguity regarding the ownership status of property in Minangkabau society whether it belonged to a father or was property of the clan managed by the niniak mamak. When a father passed away, the inheritance that should rightfully go to biological children often ended up with nephews, leading to injustice. Sheikh Ahmad Khatib's sharp criticism emphasizes the need for reform in the customary inheritance system to align it with Islamic law and protect the rights of children, thereby reducing conflict and injustice in Minangkabau society in the future.